2016
DOI: 10.3892/ijmm.2016.2646
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of an LPS-induced inflammatory response using a methanolic extract of Lagerstroemia ovalifolia to suppress the activation of NF-κB in RAW264.7 macrophages

Abstract: Abstract. Lagerstroemia ovalifolia Teijsm. & Binn. has traditionally been used as an herbal medicine and possesses anti-inflammatory properties. However, the mechanisms underlying its anti-inflammatory effects remain poorly understood. For this purpose, we aimed to investigate the effects of methanolic extract of L. ovalifolia (LOME) on nitric oxide (NO) and prostaglandin E 2 (PGE 2 ) production, as well as the underlying molecular mechanisms responsible for these effects, in lipopolysaccharide (LPS)-stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…For herbal extracts, several mechanisms of interference with the production or activity of eicosanoids have been described including the regulation of enzyme expression [8][9][10] and enzyme activity [11], but also by influencing the expression of eicosanoid receptors [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…For herbal extracts, several mechanisms of interference with the production or activity of eicosanoids have been described including the regulation of enzyme expression [8][9][10] and enzyme activity [11], but also by influencing the expression of eicosanoid receptors [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, mitogen and differentiation signals are able to activate the ERK while stress stimuli activate p38 and JNK [ 61 ]. Many studies have illustrated that the up-regulation of TNF-α, IL-1β, and IL-6 is diminished by phytochemicals through the inhibition of the activation of ERK, JNK, and p38 [ 6 , 62 ]. In this paper, MHP and linarin down-regulated the phosphorylation levels of ERK, JNK, and p38.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are phagocytic white blood cells that play an important role in innate immune inflammatory responses. Activated macrophages secrete various cytokines such as tumor necrosis factor-α (TNF-α), interlenkin-1β (IL-1β), interlenkin-6 (IL-6), and other inflammatory cytokines [ 5 ], which show pleiotropic effects via activating adaptive immune responses and worsening inflammatory responses [ 6 ]. The nuclear factor kappa-B (NF-κB) signaling pathway is involved in regulating diverse gene expression during inflammatory responses [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These subunits block IκB-α in its normal state, but upon stimulation by the inflammatory response, IκB-α undergoes phosphorylation and is degraded, while NF-κB is activated (18). LPS induces the activation of NF-κB, which then stimulates the expression of pro-inflammatory cytokines, including IL-6 and TNF-α, as well as chemokines (19). Therefore, the present study confirmed that CSME suppressed LPS-induced inflammatory mediators and cytokines, as well as phosphorylation of IκB-α and p65, in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%